Determining the Impact of Federal Antidiscrimination Policy on the Economic Status of Blacks: A Study of South Carolina - Heckman, James J.; Payner, Brook S. (American Economic Review, 1989)
This paper assesses the contribution of federal antidiscrimination policy to the dramatic improvement of black economic status in manufacturing that occurred in South Carolina in the mid 1960's. Using a unique data source on wages and employment by race and sex in South Carolina we evaluate competing explanations. Human capital stories, supply shift stories and tight labor market stories do not account for the black breakthrough. Our study documents a significant contribution of federal antidiscrimination programs.